CHARACTERIZATION AND COBALT DISTRIBUTION STUDY OF CERAMIC BODY SYSTEM : BOJONEGORO CLAY– FELDSPAR – QUARTZ - Rohmat Sulistya; Djoko Hartanto; Irmina Kris Murwani (Universitas Gadjah Mada, 2006)
The quality improvement of Bojonegoro Clay and the cobalt distribution on the surface of ceramic body system have been studied. The ceramic body system consists of Bojonegoro Clay, feldspar and quartz is optimized using a triaxial blend method. About 6 compositions among 15 compositions of synthesized ceramic bodies can be casted in plastic condition with plastic limit between 22 and 30%. It has been obtained that the optimum composition of the ceramic body is 57% clay, 14.5% feldspar, 28.5% quartz with the total shrinkage is 7 % and the modulus of rupture is 18.23 N/mm2. Cobalt is distributed homogenously on the optimum ceramic surface with 0.3 mm depth at optimum glaze firing temperature (1050 oC).